Development, item analysis, and initial reliability and validity of three forms of a multiple-choice mental health literacy assessment for college students (MHLA-c). (June 2021) - Rabin, Laura A.; Miles, Rona T.; Kamata, Akihito; Krishnan, Anjali; Elbulok-Charcape, Milushka; Stewart, Genéa; Compton, Michael T.
Highlights: The MHLA-c is a self-administered, multiple-choice mental health literacy measure The MHLA-c was validated among diverse U.S. college students Females, psychology majors, and those with mental health experience had higher scores than others The MHLA-c has three parallel forms for use within studies that employ pre-post testing designs Abstract: Despite increasing rates of mental health disorders among college students, there are a limited number of validated mental health literacy measures that can be quickly administered and scored in this population. We developed a 54-item multiple-choice measure, consisting of three forms with 18 items on each form. Our items focus on knowledge of more than 20 mental health disorders including their etiology, risk factors, diagnoses, symptoms, treatment, course, and outcome, as well as the application of this knowledge to real world situations. Data were collected on three independent samples of undergraduate students enrolled at an urban public university system in the northeast United States: pilot ( n =292), test refinement ( n =1, 272), and validation ( n =683). Basic demographics for the combined test refinement and validation samples were: age=22 ± 4.9 years; 62.2% female; 71.7% non-White. We report on the development of the Mental Health Literacy Assessment-college (MHLA-c) and provide support for its reliability and validity. We also provide descriptive statistics, stratified by gender, college major, and personal experience with a mental health issue to enable its use in diverse settings. The MHLA-c may be useful in measuring knowledge of mental health disorders and related topics among college students. Moreover, the availability of parallel forms will facilitate its use within educational or interventional studies that employ pre-post testing designs.